Teaching interactive media design - Özcan, O; Akarun, L (KLUWER ACADEMIC PUBL, 2002)
In todays, computer-centered society, designing interactive media has emerged as a new profession. Interactive design is often associated with spread of computers as a communication and interaction tool. However, interactive design has been a staple of artists and designers for many centuries. We present a historical perspective upon interactive design and point out the close relationship of this field with different fields of art and design. We argue that interactive media design is a distinct and evolving field and that it is imperative to teach it as such. In this paper, we have adopted this perspective and detailed a new four-year under-graduate curriculum on interactive media design education. This curriculum stresses the various components of interactive media design and its close relationship with computer science.
Keywords: art and design; curriculum design; interactive media; Education & Educational Research; Engineering